PEMANFAATAN STRATEGI OMNICHANNEL MARKETING DI PERGURUAN TINGGI - Hutabarat, Peny Meliaty; Altamira, Melisa Bunga; Adelina, Erni (Jurnal Vokasi Indonesia, 2021)
Technological developments encourage changes in consumer behavior, including corporate interactions. This also affects many educational institutions, especially in higher education levels. The use of multiple channels has been increasing, and it is quite a complex challenge for higher education to provide seamless and optimal journey experiences as needed by their audiences. These developments in technology and consumer behavior drive all higher education institutions to increase their competitive advantages. The omnichannel strategy is an effective way for them to increase the competitive advantage and to reach prospective students through various platforms, with specific and personified messages. In its application, omnichannel marketing strategy is often connected to Integrated Marketing Communication Concept (IMC). Hence, the channel tools utilized in omnichannel marketing strategy are platforms intersecting with the IMC communication tools. Both study and application of omnichannel marketing in the business world have frequently appeared and developed. However, study and application of omnichannel marketing in the higher education sector, especially Indonesia, are still very limited. This descriptive study aims to describe the application of omnichannel marketing in higher education contexts, by using a descriptive methodology through literature review (range 2010 – 2020). According to the study results, the application of omnichannel marketing, as a marketing communication strategy, is able to build connections and engagement with target audiences, and also to become competitive advantages for higher education institutions in this current digital technology era. Through this study, it is desired to provide an overview and insight regarding the implementation of omnichannel marketing strategies particularly in higher education institutions.